(untitled) (Research, Society and Development, 2022)
Breastfeeding is an important ally to the interaction between mother and child, as well as to the physical quality and emotional health of the mother during the puerperium, the lactation period and throughout her future life. This research aims to analyze the influence of breastfeeding on women’s health and quality of life, according to the perception of lactating women in the municipality of Vitória da Conquista - Bahia. The research was guided by the qualitative study strategy, with a descriptive character. Data collection was carried out through a semi-structured questionnaire with ten open questions. The answers were analyzed using the technique of discourse analysis and speech categorization. In view of the study, it was noted that psychological and sentimental changes are better described by the women interviewed. In addition, it is expected that the present research highlights the benefits of lactation and that actions to promote, protect and encourage breastfeeding are developed, to improve indicators and promote the benefits of breastfeeding for maternal health.